2006
DOI: 10.1260/026309206779800470
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Axis Sinusoidal Whole-Body Vibrations: Part I — How Long Should the Vibration and Rest Exposures Be for Reliable Discomfort Measures?

Abstract: Laboratory-based whole-body vibration studies often involve complex experimental designs, dozens of vibration exposures and multiple sessions. Shortening the test vibration duration would increase experimental efficiency by permitting more trials in the same time period. This study evaluated reported discomfort based on different sinusoidal vibration durations and amounts of rest between successive vibrations. Ten subjects were exposed to four blocks of vibration trials (15/20 second vibration and 5/10 second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…These acceleration levels are similar to previous studies [18][19][20]. The Vibration Total Values in the Part 1 study [21], as reported in Table I of this reference, were calculated based on chassis vibrations rather than vibration levels measured at the seatpan. Therefore, a second series of vibration exposures, which included vibration measurements at the seatpan were performed on three of the subjects from the original study (Subjects 8, 9 and 10) in order to evaluate the relationship between vibration levels at the chassis and vibration levels at the seatpan.…”
Section: Vibration System and Test Conditionssupporting
confidence: 79%
“…These acceleration levels are similar to previous studies [18][19][20]. The Vibration Total Values in the Part 1 study [21], as reported in Table I of this reference, were calculated based on chassis vibrations rather than vibration levels measured at the seatpan. Therefore, a second series of vibration exposures, which included vibration measurements at the seatpan were performed on three of the subjects from the original study (Subjects 8, 9 and 10) in order to evaluate the relationship between vibration levels at the chassis and vibration levels at the seatpan.…”
Section: Vibration System and Test Conditionssupporting
confidence: 79%
“…The subjects were exposed to 15 seconds of vibration at each frequency and experienced a 5 second resting period between tests. This duration is acceptable as found by Dickey et al [4]. The subjects rated their perceived discomfort during vibration by comparing it with their perception during the resting period.…”
Section: Subjective Reported Discomfortmentioning
confidence: 58%
“…3). Peak FTA transmissibility above one, implying amplification, occurred at 25 Hz for three participants (20,21,30), at 30 Hz for six participants (2,4,17,19,22,28), at 45 Hz for one participant (9) and 50 Hz for one participant (11) ( Table 3). Furthermore, peak FTM transmissibility above one occurred at 50 Hz for thirteen participants, while only one participant (30) had a peak greater than one at 25, 30 or 35 Hz (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…During the 45 second exposure period FTM and FTA vibration transmissibility was measured. Participants rested for 10-seconds after each 45 second vibration exposure [4].…”
Section: Vibration Exposurementioning
confidence: 99%
See 1 more Smart Citation